Challenges facing Academic Libraries in Supporting Webometrics Ranking of Universities in Kenya - Wamahiga, George M.; Kwanya , Tom; Ndegwa , Lucy (African Journal of Education,Science and Technology (AJEST), 2019)
Webometrics refers to the study of the quantitative aspects of the creation and usage of information resources, structures and technologies on the web drawing on bibliometric and infometric approaches. Across the world, libraries are committed to providing equal and rightful access to information. Therefore, libraries play a major role in influencing Webometrics ranking of universities across the world. Academic libraries influence Webometrics ranking through generation of scientific publications and other scholarly resources. Despite the remarkable success in Academic libraries’ influence on Webometrics ranking, there are a number of setbacks facing these libraries in the effective facilitation of Webometrics ranking. This study examined the challenges facing academic libraries in supporting Webometrics ranking of universities in Kenya. The study adopted a mixed research design. The researcher collected data from a representative sample of 30 % of the entire target population in University of Nairobi, Chuka University and Kirinyaga University. The selection of the three universities was based on the most recent Webometrics rankings. The respondents were drawn from library, ICT and research Departments. Primary data was collected through semi-structured questionnaires and interviews. The data was analysed using descriptive statistics that is frequency distribution tables to compute mean. The study established that Bureaucratic and connectivity barriers as well as substandard research and inadequate knowledge on Webometrics are the key challenges facing Kenyan academic libraries in supporting improved webometrics ranking. The findings of this study may be used by other institutions of higher learning on the mechanisms they can adopt to increase the capacities of their academic libraries so as to improve the contribution of these libraries to Webometrics and consequently to the overall ranking of the individual universities nationally and internationally. The findings may also help policy makers and policy implementers to effectively understand the challenges facing academic libraries in supporting Webometrics ranking of universities in Kenya and hence improve opportunities for upscaling Webometrics in academic institutions.